2012
DOI: 10.4103/1947-2714.94945
|View full text |Cite
|
Sign up to set email alerts
|

Pattern of angiotensin-converting enzyme inhibitors induced adverse drug reactions in South Indian teaching hospital

Abstract: Background:Adverse drug reactions (ADRs) occur frequently with cardiovascular drugs leading to change in therapy, increasing morbidity, and mortality.Aim:The study was conducted to evaluate the incidence of ADRs due to angiotensin-converting enzyme Inhibitors in cardiology department.Materials and Methods:A cross-sectional observational study was carried out for a period of 6 months. The data were assessed for the pattern of the ADRs with respect to patient demographics, nature of the reaction, outcome of the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(1 citation statement)
references
References 17 publications
0
1
0
Order By: Relevance
“…[ 13 14 ] Mateti et al ., also observed 58.33% of ADRs due to cardiovascular drugs in age group of more than 61 years and they suggested that age is also a factor influencing the number of ADRs. [ 15 ]…”
Section: Discussionmentioning
confidence: 99%
“…[ 13 14 ] Mateti et al ., also observed 58.33% of ADRs due to cardiovascular drugs in age group of more than 61 years and they suggested that age is also a factor influencing the number of ADRs. [ 15 ]…”
Section: Discussionmentioning
confidence: 99%